Implementation of LEAN Warehousing to Reduce Waste in Warehouse CV.X - Donoriyanto, Dwi Sukma; Syamsi, Muhammad Nabighoh Badarus; Nugraha, Isna (Tibuana, 2024)
CV. X is a company engaged in the manufacturing of various types of clothing. CV. X produces various types of clothing such as shirts, jackets, pants, and accessories. The warehouse at CV. X shows an increase when storing warehouse goods. There is waste in the form of waiting caused by goods waiting for operators to move them. There is another indication of waste in the form of a high level of transportation activities in the warehouse. The aim of this research is to help the company minimize waste in the warehouse process. This research uses the Lean Warehousing method, and improvement proposals involve implementing the 5S methodology. From the waste in the warehouse process at CV. X, the highest type of waste is waiting, with an average weighting score of 4.4, followed by excess inventories with an average weighting score of 4, and transportation with an average weighting score of 3.6. One improvement proposal suggested is to clean and rearrange the items stored in the warehouse.